PENGARUH RANSUM DENGAN PERSENTASE SERAT KASAR YANG BERBEDA TERHADAP PERFORMA AYAM JANTAN TIPE MEDIUM UMUR 3--8 MINGGU - Nurdiyanto, Rahmat; Sutrisna, Rudy; Nova, Khaira (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
Different percentages of crude fiber in rations can affect the performance type of medium rooster such as ration consumption, body weight gain, conversion ratio, and income over feed cost (IOFC). Rooster medium type is an important source of animal protein to meet their daily nutritional needs. This study aims to: (1) determine the effect of rations with different percentages of crude fiber on performance rooster type medium and (2) determine the best coarse fiber content in the diet on performance rooster type of medium. This study was conducted in 12 September until 20 October 2014 located in the cage of Rama Jaya Farm, Karang Anyar, Jati Agung court, South Lampung regency. This study used a completely randomized design (CRD) with 4 treatments and 3 replications. Ration percentage of crude fiber are R0:4%, R1:6%, R2:8%, and R3:10%. Data obtained was statistically tested to determine the effect of treatments to the variables observed by variance analysis. Then, it was continued by using Least Significant Different (LSD) on significant level 5%. The result of this study showed that (1) ration with different percentages of crude fiber was not significant (P>0.05) to ration consumption, body weight gain, conversion ratio, and income over feed cost on roosters type of medium. (2) rations with different percentages of crude fiber was give equally good effect on ration consumption, body weight gain, conversion ratio, and income over feed cost on roosters type of medium.